Problem of Understanding Drug Instructions by a Non-Specialist - N. Yu. Antonova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
This article is devoted to the problem of studying the texts used to inform the consumer in detail about the drug. The texts of instructions for the use of drugs manufactured in Russia and abroad are analyzed. The question of introducing new approaches to the development of these texts in the field of domestic pharmacy is raised. The relevance of the study is due to the need to develop special tools to ensure the successful perception and understanding of these texts by drug users. The results of the analysis of some language tools and the features of the construction (architectonics) of these texts from the standpoint of perception and understanding of their contents by an addressee who does not have special knowledge in the field of medicine and pharmacy are presented. Particular attention is paid to the consideration of tools that facilitate the reading of these texts by a non-specialist. The similarities and differences in the use of these drugs in the texts of medicinal instructions in Russian and English are shown. The conclusion is drawn about the relationship between the presence or absence in the texts of medical instructions of certain language means and structural features and the nature of perception and understanding of these texts by the addressee.